AN ASSESSMENT OF INLAND WATERWAYS OPERATIONS AND CHALLENGES ALONG COASTAL COMMUNITIES IN THE NIGER DELTA - Imorataria, D. A.; Ogola. D.B.; ThankGod. M. O., (Asian Journal of Multidisciplinary Research & Review (AJMRR)., 2024)
The purpose of this research is inland waterways transport in Nigeria face, which have an impact on both their potential for future growth and their ability to continue to contribute to the nation's economic development. Inland waterway transportation's operational difficulties in Niger Delta coastal villages were investigated. A cross-sectional research design was used for the investigation. A total of 2000 copies of a questionnaire were distributed in four Local Government Areas of Niger Delta States. Simple summary statistics including mean, media, mode, and percentages were used in this study. The study concluded that despite the major operational difficulties faced by boat owners and operators, there is still a sizable amount of passenger traffic in this type of water transportation. According to the study, government and private boat operators should offer sufficient covered speed boats and safety vests for all users, as well as a boat repair facility, intermittent dredging of waterways, the removal of wrecks and water hyacinths, stabilization of transportation costs, zero tolerance for alcohol and drugs, and speed limiter devices.
The purpose of this research is inland waterways transport in Nigeria face, which have an impact on both their potential for future growth and their ability to continue to contribute to the nation's economic development
Keywords: Transportation; Operational Challenge; Inland waterways; Boat; Niger Delta